Arbitration Ruling: Finality, Binding Force, And Legal Implications In Indonesia - Anjlan Berutu; Muhammad Said Harahap; Nazila Aulia; Putri Syifa Fazyra Nasution; Zulkarnain Iskandar (ISNU Nine-Star Multidisciplinary Journal, 2024)
In an era of globalization and increasing market complexity, dispute resolution has become a crucial aspect of the business world, with arbitration emerging as an increasingly favored alternative. This method offers flexible and efficient solutions, avoiding lengthy and costly litigation processes. Arbitration has advantages, particularly regarding finality, where its decisions are binding and generally not subject to appeal, providing highly valuable legal certainty for business actors. In Indonesia, economic growth and foreign investment necessitate an effective dispute resolution mechanism, in which the Indonesian National Arbitration Board (BANI) plays an active role in providing an arbitration platform. This study aims to analyze the principles of finality and the binding force of arbitration awards within the context of Indonesian law, as well as the legal implications related to the enforcement and potential annulment of awards. Using a normative juridical approach, this research evaluates the effectiveness of Law No. 30 of 1999 and the 1958 New York Convention. The results indicate challenges in the application of the principles of finality and the independence of arbitrators, while also providing recommendations to strengthen the arbitration system in Indonesia to enhance legal certainty and the effectiveness of dispute resolution.